Azulene-Based Organic Cages Formed with 1,3,5-Tris(aminomethyl)-2,4,6-triethylbenzene: Synthesis and Physicochemical Properties - Ion, Adrian E.; Dogaru, Andreea; Maxim, Catalin; Hanganu, Anamaria; Enache, Cristian; Andruh, Marius; Nica, Simona (Synthesis, 2025)
A novel [2+3] imine cage, derived from 1,3-diformylazulene and 1,3,5-tris(aminomethyl)-2,4,6-triethylbenzene, was synthesized and characterized. NMR spectroscopy and single crystal X-ray diffraction confirmed the formation of a symmetric hexaimine structure. The cage exhibits fluorescence, as well as characteristic azulene redox behavior. However, its stability in solution is sensitive to the acidity of the solvent. Reduction with NaBH4 led to the isolation of a more stable hexaamine cage, providing a means to further stabilize the structure.
Keywords: azulene-based cages; Schiff base; fluorescence; redox active; hexaamine macrocycle